KETEPATAN PENYUSUNAN KURIKULUM PRODI MPI FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN RADEN FATAH DIKAITKAN DENGAN KKNI, SN-DIKTI, DAN PANDUAN PENYUSUNAN KURIKULUM PENDIDIKAN TINGGI TAHUN 2014 - Nyayu Khodijah (El-Idare, 2016)
The curriculum has a strategic position and influence in the whole process and outcomes of education. Each program of study required to formulate a minimal learning outcomes description refers KKNI higher education in accordance with the level. This study uses a model curriculum evaluation Countenance. The data were analyzed qualitatively in the form of qualitative narrative analysis of documents and interviews. The results of the study, namely; (A) the coverage of document components in the curriculum, a curriculum document Prodi MPI components do not meet the minimum coverage specified by the Higher Education. (B) the formulation of graduate profiles in curriculum documents Prodi MPI, both on process and outcome, both not fully meet standards. (C) the formulation of learning outcomes in the curriculum document Prodi MPI, both on process and outcome, both not fully meet standards. (D) the distribution of subjects in the curriculum structure Prodi MPI has not fully meet the standards.